Uji Efektifitas Biji Kelor (Moringa Oleifera) Terhadap Penurunan Kadar Besi (Fe) Air Sumur Gali Di Desa Buhung Bundang Kecamatan Bontotiro Kabupaten Bulukumba - Ika Mustika; Andi Indrawati; Andi Auliyah Warsyidah (Jurnal Media Laboran, 2018)
Moringa oleifera fruit seeds contain bioactive compounds rhamonsyloxyl-benzyl-isothiocyanate, which are able to adopt and neutralize particles of mud and metals contained in water into consumable clean water, and meet established quality standards. Many people don't know that Moringa seeds can be a safer alternative water purifier. The purpose of this study was to determine the effectiveness of Moringa seeds to decrease iron (Fe) levels in dug well water with quantitative methods on UV-Vis spectrophotometers. This type of research is an experimental laboratory that was conducted in August 2017. The population used was all dug well water in Buhung Bundang Village, Bontotiro District, Bulukumba Regency. The sample used was one of the dug well water taken by using purposive sampling technique. The results of the study show that from the samples examined the average value of the percentage of degradation produced is by immersion time from 0-45 minutes as much as 45.66%, from 45-60 minutes as much as 72.12% (an increase of 26.46%) , from 60-75 minutes as much as 87.88% (an increase of 15.76%). However, the most effective time for Fe (II) ion degradation process is 60 minutes with an average degradation yield of 72.12% with an increase in degraded Fe ions of 26.46% from the results of the average immersion for 15 minutes with the addition of 5 Moringa seeds.